Transcriptome and Hormone Analysis Revealed Jasmonic Acid-Mediated Immune Responses of Potato (Solanum tuberosum) to Potato Spindle Tuber Viroid Infection - Marković, Iva; Jarić, Bernard; Oklešťková, Jana; Široká, Jitka; Majsec, Kristina; Milanović, Jasna; Kereša, Snježana; Habuš Jerčić, Ivanka; Novák, Ondřej; Mihaljević, Snježana (Antioxidants (Basel, Switzerland), 2026)
Potato is a globally important non-cereal crop in which infection with potato spindle tuber viroid (PSTVd) can cause stunted growth and significantly reduce tuber yield. We previously showed that PSTVd induces accumulation of the plant hormone jasmonic acid (JA) and alters antioxidant responses in potato plants. To clarify the role of JA in response to PSTVd, we analyzed disease development in transgenic JA-deficient opr3 and JA-insensitive coi1 lines compared to the wild-type. Transcriptomic analysis using RNA-Seq revealed that most genotype-specific differentially expressed genes (DEGs) in all comparisons were enriched in plant hormone signal transduction, plant-pathogen interaction, and MAPK signaling pathways, although the number of DEGs varied. These differences were confirmed by independent data from RT-qPCR, hormone, and hydrogen peroxide (H2O2) analyses. After PSTVd infection, opr3 plants showed enhanced JA signaling and increased abscisic acid (ABA) and auxin (AUX) content. In contrast, coi1 plants showed reduced ABA, AUX, and salicylic acid content. Both opr3 and coi1 plants showed reduced JA and H2O2 content and lower expression of defense-related genes, resulting in milder symptoms but increased viroid accumulation. In addition, treatment with methyl jasmonate alleviated symptoms in infected wild-type plants. Together, these results indicate a modulatory role for JA and JA signaling in basal immune responses and symptom development in the potato-PSTVd interaction.
Keywords: biotic stress; potato; hormone crosstalk; growth–defense trade-off; MeJA; antioxidant responses; basal defense responses; jasmonic acid; RNA-Seq; PSTVd